The language of the individual in the paralles of Abeghyan’s language standardization - Aghajanyan, Zarik (Bulletin of Yerevan University B: Philology, 2024)
Abeghyan is a member of tne youth grammar school. According to him, the laws of language are similar to the lows of nature and society. It changes, and the individual maks those changes. Every individual, motivated by the need of the moment, changes the language, which can lead to the change of the normative system of the language. The famous Armenologist considers the language of an individual as a concrete expression of an abstract. M. Abeghyan’s theory of individual languages is directly releted to the problems of modern general linguistics, such as the origin of language, the development of the pre-language, the emergence of related languages. The great lingvist connects the change of language whit an individual’s education, his knowledge of the word, language education, language taste, cultural values. Abeghyan is also an outstanding personality of the Armenian people, as a linguist, as a scientist, as a theacher and pedagogue, as a literary critic. He is rightly <<The giant (oak) of Armenian linguistics>>.